2016
DOI: 10.1007/s00011-016-0964-8
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 induces autophagy to control AIEC bacteria infectiveness in intestinal epithelial cells

Abstract: The NOD2-mediated autophagy induction is crucial to hold the intramucosal bacterial burden, especially towards AIEC, and to limit the resulting inflammatory response. Autophagy is active in inflamed colonic tissues of IBD pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 44 publications
0
27
0
1
Order By: Relevance
“… 13 In humans and experimental animals, it has emerged that genetic defects in bacterial sensing and killing (eg, NOD2, ATG16L ) are frequently associated with IBD. 15 17 Variants in these genes are associated with downstream effects on protein function and, subsequently, clinical disease. 15 17 Recent studies in Boxer dogs and French Bulldogs with GC have identified a region in chromosome 38 encoding genes in the signaling lymphocyte activation molecule family that are involved in the sensing and killing of E coli in murine models.…”
Section: Discussionmentioning
confidence: 99%
“… 13 In humans and experimental animals, it has emerged that genetic defects in bacterial sensing and killing (eg, NOD2, ATG16L ) are frequently associated with IBD. 15 17 Variants in these genes are associated with downstream effects on protein function and, subsequently, clinical disease. 15 17 Recent studies in Boxer dogs and French Bulldogs with GC have identified a region in chromosome 38 encoding genes in the signaling lymphocyte activation molecule family that are involved in the sensing and killing of E coli in murine models.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recent studies have identified that NOD2-mediated induction of autophagy in intestinal epithelial cells was necessary to hold bacterial burden, thereby limiting inflammation [23]. NOD2 was identified as one of the inflammatory bowel disease susceptibility genes involved in autophagy [24,25].…”
Section: Crosstalk Between Autophagy and The Inflammasome Machineriesmentioning
confidence: 99%
“…36,37 A number of genes in IBD susceptibility loci restrict intracellular bacteria, including ATG16L1, NOD2, IRGM, CALCOCO2/NDP52, and GPR65, suggesting that antibacterial autophagy is a major pathway underlying intestinal homeostasis in vivo. 5,31,[38][39][40][41] These genes function in various steps of the antibacterial autophagy cascade, including bacterial sensing (NOD2), bacterial targeting (IRGM, CALCOCO2), autophagosome elongation (ATG16L1), and lysosomal function (GPR65). The interaction between NOD2 and ATG16L1 in antibacterial autophagy has been of particular interest and this interaction is thought to be important for bacterial clearance and increased cytokine release.…”
Section: Autophagy and The Control Of Intestinal Microbesmentioning
confidence: 99%